Partial Differential Equations-Based Segmentation for Radiotherapy Treatment Planning - Frédéric Gibou; Doron Levy; Carlos Cárdenas; Pingyu Liu; Arthur Boyer (Mathematical Biosciences and Engineering)
The purpose of this study is to develop automatic algorithms for the segmentation phase of radiotherapy treatmentplanning. We develop new image processing techniques that are based on solving a partial differential equation for theevolution of the curve that identifies the segmented organ. The velocity function is based on the piecewiseMumford-Shah functional. Our method incorporates information about the target organ into classical segmentationalgorithms. This information, which is given in terms of a three-dimensional wireframe representation of the organ,serves as an initial guess for the segmentation algorithm. We check the performance of the new algorithm on eight datasets of three different organs: rectum, bladder, and kidney. The results of the automatic segmentation were comparedwith a manual segmentation of each data set by radiation oncology faculty and residents. The quality of the automaticsegmentation was measured with the ''$κ$-statistics'', and with a count of over- and undersegmented frames, andwas shown in most cases to be very close to the manual segmentation of the same data. A typical segmentation of anorgan with sixty slices takes less than ten seconds on a Pentium IV laptop.